Obelia geniculata - Calder, Dale R. (Zenodo, 2013)
Obelia geniculata (Linnaeus, 1758) Fig. 16e Sertularia geniculata Linnaeus, 1758: 812. Type locality. UK: Dover. According to Cornelius (1975), Linnaeus (1758) is likely to have established this species based on an illustration of material from Dover, England, by Ellis (1755). Voucher material. Off Fort Pierce, between Capron Shoal and the beach, on Thyroscyphus ramosus , 09.v.1974, SCUBA, two colonies, up to 7 mm high, with one empty gonotheca, coll. D. Biggs and D. Mook, ROMIZ B1073.— Hutchinson Island, Walton Rocks area, 27°20’19”N, 80°13’59”W, on algae, 17.ii.1991, collected manually, one colony, up to 5 mm high, with gonophores, coll. D.R. Calder, ROMIZ B1107.— Fort Pierce Inlet, north jetty, north side, 27°28’24.2”N, 80°17’20.3”W, on Thyroscyphus ramosus , 0.1 m, 15.ii.1991, 20° C, collected manually, two colonies, up to 8 mm high, with gonophores, coll. D.R. Calder, ROMIZ B1115.— Sebastian Inlet, 27°51’43”N, 80°26’47”W, washed ashore on Sargassum , 19.ii.1991, collected manually, one colony, up to 5 mm high, without gonophores, coll. D.R. Calder, ROMIZ B1119. Remarks. While often thought to be virtually cosmopolitan in shallow waters, molecular studies (Govindarajan et al . 2005) suggest the existence of cryptic species in hydroids of the Obelia geniculata (Linnaeus, 1758) morphotype. Moreover, the reported latitudinal distribution of O. geniculata , from the subarctic to the tropics, also appears to be exceptionally wide for a single species. Within that geographic range, local morphological variants have been noted. In one example, populations from Chesapeake Bay lack the usual asymmetrical development of perisarc on internodes of the hydrocaulus (Calder 1971), considered characteristic of the species (Cornelius 1995b). Hydroids from Florida examined here had the typical asymmetric thickening of perisarc on stem internodes beneath the distal hydrotheca on each, but colonies appeared to be stunted compared with those from boreal waters of the western and eastern North Atlantic (Calder 1975, 2012). Reported distribution. Atlantic coast of Florida. First record. Western Atlantic. Hudson Strait (Fraser 1944) to Argentina (Oliveira et al . submitted), and from the Gulf of Mexico (Joyce 1961; Calder & Cairns 2009) and Caribbean Sea (Vervoort 1968, as Laomedea ( Obelia ) geniculata ). Elsewhere. Considered essentially cosmopolitan in neritic waters (Vervoort & Watson 2003). : Published as part of Calder, Dale R., 2013, Some shallow-water hydroids (Cnidaria: Hydrozoa) from the central east coast of Florida, USA, pp. 1-72 in Zootaxa 3648 (1) on pages 57-58, DOI: 10.11646/zootaxa.3648.1.1, http://zenodo.org/record/5264362 : {"references": ["Linnaeus, C. (1758) Systema naturae per regna tria naturae, secundum classes, ordines, genera, species cum characteribus, differentiis, synonymis, locis. Editio decima, reformata. Laurentii Salvii, Holmiae, 823 pp.", "Cornelius, P. F. S. (1975) A revision of the species of Lafoeidae and Haleciidae (Coelenterata: Hydroida) recorded from Britain and nearby seas. Bulletin of the British Museum (Natural History), Zoology, 28, 375 - 426.", "Ellis, J. (1755) An essay towards a natural history of the corallines, and other marine productions of the like kind, commonly found on the coasts of Great Britain and Ireland. Printed for the author, London, 104 pp.", "Govindarajan, A. F., Halanych, K. M. & Cunningham, C. W. (2005) Mitochondrial evolution and phylogeography in the hydrozoan Obelia geniculata (Cnidaria). Marine Biology, 146, 213 - 222. http: // dx. doi. org / 10.1007 / s 00227 - 004 - 1434 - 3", "Calder, D. R. (1971) Hydroids and hydromedusae of southern Chesapeake Bay. Virginia Institute of Marine Science, Special Papers in Marine Science, 1, 1 - 125.", "Cornelius, P. F. S. (1995 b) North-west European thecate hydroids and their medusae. Part 2. Sertulariidae to Campanulariidae. Synopses of the British Fauna, new series, 50, 386 pp.", "Calder, D. R. (1975) Biotic Census of Cape Cod Bay: hydroids. Biological Bulletin, 149, 287 - 315. http: // dx. doi. org / 10.2307 / 1540528", "Calder, D. R. (2012) On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region. Zootaxa, 3171, 1 - 77.", "Fraser, C. M. (1944) Hydroids of the Atlantic coast of North America. University of Toronto Press, Toronto, 451 pp.", "Joyce, E. A. Jr. (1961) The Hydroida of the Seahorse Key area. M. S. Thesis, University of Florida, Gainesville, 116 pp.", "Calder, D. R. & Cairns, S. D. (2009) Hydroids (Cnidaria: Hydrozoa) of the Gulf of Mexico. In: Felder, D. L. & Camp, D. K. (Eds.), Gulf of Mexico. Origin, waters, and biota. Vol. 1. Biodiversity. Texas A & M University Press, College Station, pp. 381 - 394.", "Vervoort, W. (1968) Report on a collection of Hydroida from the Caribbean region, including an annotated checklist of Caribbean hydroids. Zoologische Verhandelingen, 92, 1 - 124.", "Vervoort, W. & Watson, J. E. (2003) The marine fauna of New Zealand: Leptothecata (Cnidaria: Hydrozoa) (thecate hydroids). National Institute of Water and Atmospheric Research Biodiversity Memoir, 119, 1 - 538."]}